2017
DOI: 10.1080/03008207.2016.1271797
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of adult mouse meniscus stem/progenitor cells

Abstract: Meniscal damage is a common problem that accelerates the onset of knee osteoarthritis. Stem cell-based tissue engineering treatment approaches have shown promise in preserving meniscal tissue and restoring meniscal function. The purpose of our study was to identify meniscus-derived stem/progenitor cells (MSPCs) from mouse, a model system that allows for in vivo analysis of the mechanisms underlying meniscal injury and healing. MSPCs were isolated from murine menisci grown in explant culture and characterized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Recently, meniscus stem/progenitor cells have been considered as the most suitable cell type for meniscus injury repair due to them having the same tissue origin and histocompatibility,36 37 however, the characteristics, marker genes and isolation methods of human meniscus progenitor cells have not yet been fully elucidated. Gamer et al isolated meniscus progenitor cells from mice meniscus grown in explant cultures, and carried out flow cytometry analysis to show that these cells highly expressed CD44 and Sca-1 7. Shen et al digested human meniscus using collagenase and seeded the cells at a low density to form colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, meniscus stem/progenitor cells have been considered as the most suitable cell type for meniscus injury repair due to them having the same tissue origin and histocompatibility,36 37 however, the characteristics, marker genes and isolation methods of human meniscus progenitor cells have not yet been fully elucidated. Gamer et al isolated meniscus progenitor cells from mice meniscus grown in explant cultures, and carried out flow cytometry analysis to show that these cells highly expressed CD44 and Sca-1 7. Shen et al digested human meniscus using collagenase and seeded the cells at a low density to form colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, stem/progenitor cells were suggested to be present in the meniscus to promote meniscus injury repair 5 6. Gamer et al isolated meniscus stem/progenitor cells by meniscus explant culture in vitro, characterising these cells with clonogenicity properties and abundantly expressed CD44 and Sca-1 7. However, the cell-type composition and cell distribution in the menisci, as well as biochemical markers for meniscus stem cell/progenitor for use in tissue engineering, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cell surface markers associated with progenitor cells were found both surrounding the vasculature and in the superficial zone of the meniscus tissue, suggesting the presence of progenitor cells in these regions. Moreover, Gamer and colleagues identify and characterize a novel population of meniscus-derived stem/progenitor cells in the mouse (10). Further research is necessary to learn more about these endogenous meniscus stem/progenitor cells but it is tempting to believe that they could be activated in order to help facilitate repair of injured meniscus tissue.…”
mentioning
confidence: 99%
“…Similarly, another study showed that MSCs isolated from rabbit menisci have universal stem cell characteristics, including clonogenicity, multipotency, self-renewal capacity, and expression of stem cell markers, and a pronounced tendency to chondrogenic differentiation appeared both in vivo and in vitro compared to that of bone marrow-derived stem cells (BMSCs) [19]. Gamer et al [20] isolated and localized stem/progenitor cells from murine menisci grown in explant culture, and localization studies suggested that endogenous progenitor cells may reside in the superficial and outer regions of the meniscus in vivo.…”
Section: In Meniscusmentioning
confidence: 98%